PENGARUH PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP HASIL BELAJAR MATERI AKULTURASI BUDAYA LOKAL KELAS V SD NEGERI 200 PALEMBANG - Listriani, Regita; Nuzulia Armariena , Dian; Marleni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the impact of implementing the "abyss board" learning medium on students' academic achievement in mathematics, particularly in the domain of addition and subtraction at the second grade of elementary school. A quantitative approach was employed using a pre-experimental design with a one-group pretest-posttest model. The study population consisted of all second-grade students at SD Negeri 91 Palembang, totaling 80 students. Sample selection was conducted through non-probability sampling using purposive sampling technique, resulting in a single class serving as the research subject. Data were gathered through written assessments (pre-test and post-test), observational records, and learning documentation. The findings revealed a notable improvement in student learning outcomes, with the mean score rising from 43.33 in the pre-test to 80.00 in the post-test. Hypothesis testing via paired sample t-test yielded a significance value of 0.000, well below the 0.05 threshold, confirming that the abyss board medium exerts a meaningful positive influence on student achievement. These results demonstrate that this instructional medium is effective in enhancing second-grade elementary students' mathematical competence in addition and subtraction.